Comparisons in ambulatory physical activity in children from the United Kingdom and Belgium. (May 2015) - Duncan, Michael J.; Birch, Samantha L.; Eyre, Emma; Bryant, Elizabeth; Rutten, Cindy; Boen, Filip; Seghers, Jan
Abstract Aim: This study sought to examine ambulatory physical activity levels in adolescents from the UK and Belgium. Methods: Following ethics approval, 2760 children (1247 boys, 1513 girls), aged 9–14 years from Belgium (n = 1614) and the UK (n = 1146), wore a pedometer for 4 days including at least 1 weekend day. Body mass index (BMI) was determined from height and mass. Results: A 2 (gender) × 2 (country) way ANCOVA, controlling for age and BMI, revealed a significant country-by-gender interaction for steps/day (p = 0.0001). In both Belgium and the UK, boys were more physically active than girls (both p = 0.0001), but the difference between boys and girls was greater for Belgian than UK children. Conclusion: These results suggest there are differences in the ambulatory physical activity patterns of children in the UK and Belgium.